Effects of lisdexamfetamine alone and in combination with s‐citalopram on acetylcholine and histamine efflux in the rat pre‐frontal cortex and ventral hippocampus - Hutson, Peter H.; Heins, Mariette S.; Folgering, Joost H.A. (Journal of neurochemistry, 2015)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by poor attention, impulse control and hyperactivity. A significant proportion of ADHD patients are also co‐morbid for other psychiatric problems including mood disorders and these patients may be managed with a combination of psychostimulants and anti‐depressants. While it is generally accepted that enhanced catecholamine signalling via the action of psychostimulants is likely responsible for the cognitive improvement in ADHD, other neurotransmitters including acetylcholine and histamine may be involved. In the present study, we have examined the effect of lisdexamfetamine dimesylate (LDX), an amphetamine pro‐drug that is approved for the treatment of ADHD on acetylcholine and histamine efflux in pre‐frontal cortex and hippocampus alone and in combination with the anti‐depressant s‐citalopram. LDX increased cortical acetylcholine efflux, an effect that was not significantly altered by co‐administration of s‐citalopram. Cortical and hippocampal histamine were markedly increased by LDX, an effect that was attenuated in the hippocampus but not in pre‐frontal cortex when co‐administered with s‐citalopram. Taken together, these results suggest that efflux of acetylcholine and histamine may be involved in the therapeutic effects of LDX and are differentially influenced by the co‐administration of s‐citalopram. Attention deficit hyperactivity disorder (ADHD) is characterized by poor attention, impulse control and hyperactivity. Some ADHD patients are also co‐morbid for mood disorders and may be managed with psychostimulants (e.g. lisdexamfetamine, LDX) and anti‐depressants (e.g. s‐citalopram). LDX increased the efflux of acetylcholine and histamine, neurotransmitters involved in cognitive function, which were differentially influenced when co‐administered with s‐citalopram. Acetylcholine and histamine may be involved in the therapeutic effects of LDX and are differentially affected by the co‐administration of s‐citalopram. Attention deficit hyperactivity disorder (ADHD) is characterized by poor attention, impulse control and hyperactivity. Some ADHD patients are also co‐morbid for mood disorders and may be managed with psychostimulants (e.g. lisdexamfetamine, LDX) and anti‐depressants (e.g. s‐citalopram). LDX increased the efflux of acetylcholine and histamine, neurotransmitters involved in cognitive function, which were differentially influenced when co‐administered with s‐citalopram. Acetylcholine and histamine may be involved in the therapeutic effects of LDX and are differentially affected by the co‐administration of s‐citalopram.